Phosphorus Vacancy‐Induced Built‐In Electric Field for Electromagnetic Properties Modulation - Yu Zhang; Pengfei Hu; Pei‐Yan Zhao; Bo Cai; Hualong Peng; Shu‐Hao Yang; Martin C. Koo; Chenming Liang; Guang‐Sheng Wang (Advanced Science)
Abstract Anion vacancy engineering represents an effective strategy to construct built‐in electric fields (BIEFs) for the purpose of modulating electromagnetic (EM) properties. However, the in‐depth and systematic comparative analysis of the effects of various anionic vacancies on defect‐induced polarization is still lacking. In this work, the effects of defect‐induced polarization resulting from group VA anion vacancies, particularly phosphorus vacancies (VP), are compared to the anion vacancies of other elements. The EM property modulation mechanisms and quantitative structure‐property relations of NiCo0.5Fe0.5P1‐x with varying contents of VP are investigated. It is concluded that the high content of VP establishes more intense BIEFs, forming permanent induced dipoles that function as polarization centers, thus enhancing defect‐induced polarization and improving permittivity and dielectric loss. NiCo0.5Fe0.5P1‐x3 with a high content of VP exhibits significant reflection loss (RL) with multi‐band compatibility and wide effective absorption bandwidth (EAB) covering the whole X‐band. This work offers a constructive perspective on the exploration of anionic vacancies from group VA, particularly VP, in modulating EM properties. Additionally, it addresses the issue of incompatibility associated with multi‐band strong microwave absorption (MA) and offers a viable strategy for designing advanced metal phosphide MA materials.